When one's birthday opens up a cosmological Pandora's box - Bautista, Julius (Philippine Studies: Historical and Ethnographic Viewpoints, 2016)
The common way of inquiring about someone's birthday in Binisaya is to ask, kanus-a ka na tawo? - literally, when did you become a person? It is an intriguing feature of the Visayan worldview, one that may well be rooted in an ancient cosmological order, that the quintessential stage of one's personhood is intuitively located not at conception but at the point in which we emerge into the world, when we take our first breath and attain independent physical viability.